Assessing Decentralized Contract Life Cycle Management Issues and Challenges - Ampumuza, Gracious Jean; Okaka, Wilson; Obanda, Peter W.; Watmon, Titus Bitek (Journal of Human, Earth, and Future, 2020)
This article examines the influence of contract life cycle management on procurement performance of Local Governments in Uganda using Bugiri District as the case study. The three specific objectives of this study were to: examine the influence of contract creation on procurement performance; to assess the influence of contract execution on procurement performance and lastly, to determine the influence of contract analysis on procurement performance. The researcher employed a descriptive case study research design. Using a researcher’s made five point Likert scale questionnaire, data was collected from a sample of respondents. Seventy (70) respondents out of a population of eighty (80) were selected using purposive and random sampling techniques (response rate of 94.3%). Data was analyzed using means and the regression analysis. Findings revealed that; the extent to which contract creation predicts performance was low (r2 = 0.36, Sig. Value= 0.000); the extent to which contract execution influences procurement performance was low (r2 = 0.34, Sig. Value = 0.003) and lastly, the extent to which contract analysis influences procurement performance was moderate (r2 =0.44, Sig. Value = 0.001). On the other hand, findings revealed that contract management at Bugiri District local government in Uganda highly and positively influences procurement performance (R2= 0.779 Sig. Value= 0.000). This implies that where each of these variables; contract creation, execution and analysis are handled separately, each has a low influence on procurement performance. However if handled wholesomely, results show that high procurement performance (78%) will be achieved. In light of this, the researcher therefore concludes that; practioneers, managers and civil servants at Bugiri District should adopt a holistic approach in contract management, if procurement performance is to be maximized.
Keywords: Contract Life Cycle Management; Procurement; Contract Creation; Contract Execution; Contract Analysis; Service Delivery